2012
DOI: 10.1186/1471-2407-12-587
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of imatinib, cisplatin and 5-fluoruracil or capecitabine in advanced esophageal and gastric adenocarcinoma

Abstract: BackgroundDespite all benefit provided by established therapies prognosis of gastric cancer remains poor. Targeted inhibition of platelet derived growth factor receptor (PDGFR) by imatinib may influence tumor growth and amplify chemotherapeutic effects.MethodsThis phase I study evaluated dose limiting toxicity (DLT) of imatinib combinated with chemotherapy according to a 3-patient cohort dose-escalating design. Thirty-five patients received cisplatin (60 mg/m2 d1 q 3w)/ capecitabine (1250 mg/m2 bid d1-14 q 21)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, it is very important to find a target agent that has synergistic effects while reducing toxicity of cytotoxic agents. Clinical studies on the combination of imatinib, cisplatin and 5-fluoruracil or capecitabine have been reported (42). In one of these clinical trials, the safety and tolerability of combination of imatinib plus 5-fluoruracil was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important to find a target agent that has synergistic effects while reducing toxicity of cytotoxic agents. Clinical studies on the combination of imatinib, cisplatin and 5-fluoruracil or capecitabine have been reported (42). In one of these clinical trials, the safety and tolerability of combination of imatinib plus 5-fluoruracil was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…This hinderance on an otherwise huge success story leaves remaining research into combating BCR-ABL. In recent times, imatinib has been shown to provide synergistic anti-tumour effects when used in combination with cobalt complexes [71] and cisplatin [72][73][74][75]. Due to this, one strategy that has been utilised to circumvent resistance and dose-limiting side effects is to conjugate the BCR-ABL TKi's to metallic moieties in a similar fashion used to target EGFR above.…”
Section: Complexes Targeting Bcr-abl and Pdgfr (Platelet Derived Grow...mentioning
confidence: 99%
“…The global incidence rate of EAC is approximately 0.7/100,000 person-years, and the 5-year survival rate is merely less than 20%, although multidisciplinary treatments have been applied, including esophagectomy, radiation, and chemotherapy ( Arnold et al, 2015 ; Markar et al, 2017 ; Smyth et al, 2017 ; Zhao et al, 2019 ). Considering the chemotherapeutic resistance, several targeted agents have been applied in patients with EAC, such as imatinib ( Mayr et al, 2012 ). Unfortunately, the efficacy is still not satisfactory.…”
Section: Introductionmentioning
confidence: 99%